Role of Inactive and Active Trypanosoma cruzi Trans-sialidases on T Cell Homing and Secretion of Inflammatory Cytokines - Freire-de-Lima, Leonardo; Gentile, Luciana B.; Fonseca, Leonardo M. da; da Costa, Kelli M.; Santos Lemos, Jessica; Jacques, Lucas Rodrigues; Morrot, Alexandre; Freire-de-Lima, Célio G.; Nunes, Marise P.; Takiya, Christina M.; Previato, Jose O.; Mendonça-Previato, Lucia (Frontiers in Microbiology, 2017)
trans-Sialidase from Trypanosoma cruzi (Tc-TS) belongs to a superfamily of proteins that may have enzymatic activity. While enzymatically active members (Tc-aTS) are able to transfer sialic acid (SIA) from the host cell sialyl-glycoconjugates onto the parasite or to other molecules on the host cell surface, the inactive members (Tc-iTS) are characterized by their lectinic properties. Over the last ten years, several papers demonstrated that, individually, Tc-aTS or Tc-iTS is able to modulate several biological events. Since the genes encoding Tc-iTS are present in the same copy number as those encoding Tc-aTS, and both proteins portray similar substrate-specificities as well, it would be plausible to speculate that such molecules may compete for the same sialyl-glycan structures and govern numerous immunobiological phenomena. However, their combined effect has never been evaluated in the course of an acute infection. In this study, we investigated the ability of both proteins to modulate the production of inflammatory signals, as well as the homing of T cells to the cardiac tissue of infected mice, events that usually occur during the acute phase of T. cruzi infection. The results showed that the intravenous administration of Tc-iTS, but not Tc-aTS protected the cardiac tissue from injury caused by reduced traffic of inflammatory cells. In addition, the ability of Tc-aTS to modulate the production of inflammatory cytokines was attenuated and/or compromised when Tc-iTS was co-injected in the same proportions. These results suggest that although both proteins present structural similarities and compete for the same sialyl-glycan epitopes, they might present distinct immunomodulatory properties on T cells following T. cruzi infection.